Strain Induced Metal–Insulator Transition of Magnetic SrRuO3 Single Layer in SrRuO3/SrTiO3 Superlattice - Angus Huang; Sheng-Hsiung Hung; Horng-Tay Jeng (Applied Sciences, 2018)
Ferromagnetic phase in a two-dimensional system plays an important role not only in applications but also in studies of phase transition theory. Among numerous ferromagnetic materials, <semantics> Sr Ru O 3 </semantics> is famous for its half-metallicity, itinerant ferromagnetism and non-Fermi liquid metalicity. Single layer <semantics> Sr Ru O 3 </semantics> in <semantics> Sr Ru O 3 </semantics> / <semantics> Sr Ti O 3 </semantics> (SRO/STO) superlattice has been predicted as a two-dimensional half-metallic ferromagnetic system based on density functional theory (DFT). However, experiments show that metal⁻insulator transition associated with ferro⁻antiferromagnetism (FM⁻AFM) transition occurs when the thickness of SRO is less than 4 u.c. Combining DFT calculations with Monte Carlo simulations, we demonstrate in this work that the bulk ferromagnetic metallicity can be realized in single layer SRO in SRO/STO superlattice by manipulating the strain effect to trigger the metal⁻insulator transition, achieving two-dimensional (2D) half-metallic SRO thin film beyond the experimental observation of AFM insulator.Our results pave a new route to fulfill the ultrathin spin-polarized-2D electron gas (SP-2DEG).